Life-time prediction for polymer materials - Chinh, Nguyen Thuy; Hoang, Thai (Vietnam Journal of Science and Technology, 2021)
Polymer testing including natural, accelerated testing or creep and fatigue testing, etc. is very important to evaluate the changes in properties, structure, morphology and durability of polymer materials. This is also the basis for experts to predict life-time or service working life or safe working life of polymer materials. This review presents an overview of the life-time prediction for polymer materials owing to natural tests or accelerated ageing tests and the methods for extrapolation of data from induced thermal degradation.